OPTIMISASI PENGIRIMAN OPTIMASI PENGIRIMAN PRODUK KALIGRAFI NIRWANA ARTWORK MENGGUNAKAN METODE TRANSPORTASI - lestari, septya dwi (Jurnal Teknologi Informasi, 2025)
Nirwana Artwork is a business engaged in the production and sale of custom calligraphy online through various e-commerce platforms. As demand from various regions in Indonesia increases, shipping costs have become a crucial component in business operations. This study aims to optimize product delivery to several destination cities using transportation methods to obtain a minimum total shipping cost. The data used includes shipping costs from three expeditions (J&T, JNE, and SiCepat) to the destination cities (Semarang, Surabaya, Yogyakarta, and Bandung), as well as the number of requests and capacity of each expedition. The solution was carried out using the Northwest Corner method for the initial solution and Stepping Stone for the solution improvement. The calculation results show that transportation methods can significantly reduce shipping costs. This optimization is expected to help MSMEs in making more efficient and economical logistics decisions.